2021
DOI: 10.2166/nh.2021.062
|View full text |Cite
|
Sign up to set email alerts
|

Water table variations on different land use units in a drained tropical peatland island of Indonesia

Abstract: Restoration and water table control on peatlands to limit fire risk are national priorities in Indonesia. The present study was initiated at Padang Island, Sumatra, to increase understanding on peatland hydrology in the tropic. At the pilot site, water table and precipitation were monitored at different stations. The results show variation in water table depths (WTDs) over time and space due to spatial and temporal variability in rain intensity and drainage networks. In part of the island, large-scale drainage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In a place where more than 3 months of inundation on the bunded area is unacceptable, it is suggested to drain the storage of the bunded area in the wet period but allow it to fill fully at the beginning of the Early Dry period. Keeping the peatland sufficiently wet (Evers et al, 2017; Ismail et al, 2021) and maintaining peatland water tables near to the surface should reduce fire risk (Page et al, 2009; Wösten et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In a place where more than 3 months of inundation on the bunded area is unacceptable, it is suggested to drain the storage of the bunded area in the wet period but allow it to fill fully at the beginning of the Early Dry period. Keeping the peatland sufficiently wet (Evers et al, 2017; Ismail et al, 2021) and maintaining peatland water tables near to the surface should reduce fire risk (Page et al, 2009; Wösten et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Padang Island's topography is generally flat, with a maximum elevation of 15 m above mean sea level (MSL), and nearly all settlements are situated at altitudes lower than 6 m above MSL. Several researchers have conducted their study here [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2a and b illustrates the traditional methods of reaching the location. Nevertheless, several researchers have conducted studies there, as indicated by the following references [9,11]. The Indonesian government, through Peatland Restoration Agency-Badan Restorasi Gambut (BRG), now known as Peatland and Mangrove Restoration Agency-Badan Restorasi Gambut dan Mangrove (BRGM) -of the Republic of Indonesia, has selected it as a pilot project for monitoring.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in land uses of tropical peatlands result in diversity in peatland characteristics. Generally, agricultural development is always accompanied by the construction of drainage channels, causing a decrease in the water table of tropical peatlands (Ismail et al 2021). Changes in the water table ultimately cause a shift in the biochemical reactions of peat decomposition, which initially occurred in anoxic conditions to become oxic conditions (Marwanto et al 2019).…”
Section: Introductionmentioning
confidence: 99%